Constrained controllability of linear retarded dynamical systems - Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
The main purpose of the paper is to study the constrained controllability for linear, time-invariant retarded dynamical systems defined in infinite-dimensional Banach or Hilbert spaces. First the brief theory of such dynamical systems is recalled. N ext, different definitions of controllability are presented and the relationships between them are explained.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka